Penerapan Aplikasi Kasir Berbasis Web Pada Percetakan Grafika Tungga Jaya - Tintin Harlina; Nur Ahmadi Indartono; Mohamad Ulin Nuha (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2026)
At the Tungga Jaya Graphic Printing Company, a manual transaction recording system is still used. Problems such as calculation errors, late reporting, and difficulty finding transaction data frequently arise. The purpose of this research is to use a web-based cashier application to improve efficiency and accuracy in managing sales data. Requirements analysis, system design, implementation, testing, and evaluation are all stages in the Waterfall System Development Life Cycle (SDLC) model. The PHP programming language and MySQL database were used to create this system. Implementation results indicate that the web-based cashier application can accelerate printing operations. The average transaction processing time was reduced from 5–8 minutes with the manual method to 2–3 minutes with the system, representing an efficiency increase of approximately 44.8%. Daily sales reports, which previously required 25 minutes, can be automatically generated in less than 5 minutes, resulting in a time savings of approximately 80%. The results of this application indicate that implementing a web-based cashier application at the Tungga Jaya Graphic Printing Company can improve work efficiency, enhance data accuracy, and enhance service quality. This system can also be a digitalization solution for small and medium-sized printing businesses (UMKM).